2020
DOI: 10.1177/0956797619896357
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Real-Life Self-Control From Brain Activity Encoding the Value of Anticipated Future Outcomes

Abstract: Deficient self-control leads to shortsighted decisions and incurs severe personal and societal costs. Although neuroimaging has advanced our understanding of neural mechanisms underlying self-control, the ecological validity of laboratory tasks used to assess self-control remains largely unknown. To increase ecological validity and to test a specific hypothesis about the mechanisms underlying real-life self-control, we combined functional MRI during value-based decision-making with smartphone-based assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 44 publications
5
29
0
Order By: Relevance
“…In accordance with this idea, higher error-related brain activity in the salience network has been found to predict lower rates of desire enactment in real-life self-control situations (Krönke et al, 2018). Increased salience detection and performance-monitoring may cause stronger recruitment of cognitive control networks, which in turn leads to increased top-down modulation of neural value signals by long-term goals and, thus, less impact of immediate desires on behavioral choices (Krönke et al, 2020). Together with converging evidence that acute stress is associated with activation of the salience network, but not always with changes in the control network (Van Oort et al, 2017), our present findings are consistent with the idea that chronic stress does not primarily impair inhibitory selfcontrol processes during acute conflicts, but rather increases the impact of immediate relative to anticipated desires on behavioral choices.…”
Section: No Evidence For Stress-related Impairments Of Resistancementioning
confidence: 62%
“…In accordance with this idea, higher error-related brain activity in the salience network has been found to predict lower rates of desire enactment in real-life self-control situations (Krönke et al, 2018). Increased salience detection and performance-monitoring may cause stronger recruitment of cognitive control networks, which in turn leads to increased top-down modulation of neural value signals by long-term goals and, thus, less impact of immediate desires on behavioral choices (Krönke et al, 2020). Together with converging evidence that acute stress is associated with activation of the salience network, but not always with changes in the control network (Van Oort et al, 2017), our present findings are consistent with the idea that chronic stress does not primarily impair inhibitory selfcontrol processes during acute conflicts, but rather increases the impact of immediate relative to anticipated desires on behavioral choices.…”
Section: No Evidence For Stress-related Impairments Of Resistancementioning
confidence: 62%
“…As mentioned above, it would also be of interest to examine the connection between PM and the actual neural implementation of self-control and how that in turn relates to goal-directed behavior in daily life. It has been suggested that the exertion of self-control is implemented via the top-down-modulation of task-relevant perceptual representations in conflict tasks (e.g., the Stroop task) (Kerns et al, 2004;Krönke et al, 2018) and of value representations in choice conflict tasks (Hare et al, 2009;Krönke et al, 2020) by goal representations maintained in the dorsolateral prefrontal cortex. Moreover, such top-down modulations have been shown to predict real-life self-control.…”
Section: Discussionmentioning
confidence: 99%
“…Data were collected as part of a prospective-longitudinal community study within a Collaborative Research Centre (SFB 940) at the Technische Universität Dresden, Germany. At baseline, participants took part in four different test sessions including a clinical assessment, a behavioural task battery, an fMRI session, and experience sampling for daily self-control failures (for further results, see Krönke et al 2018;Krönke et al 2020;Wolff et al 2016). The 1-year follow-up included only a clinical assessment.…”
Section: Design and Proceduresmentioning
confidence: 99%